The Fear of Movement/Pain in Musculoskeletal Pain-A Review - Behnam Akhbari; Sharzad Mohammadi-Raad; Mahyar Salavati (Journal of Rehabilitation, 2012)
Objective: To investigate and review psychological influences of pain such as kinesiophobia and pain-related fear on patients with musculoskeletal pain and on rehabilitation outcomes.